Affordable Homeownership Policy: Implications for Housing Markets - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2009)
Affordable homeownership is a policy that is often accorded a great deal of policy attention by governments of many countries. In this paper, we examine the market implications of setting a housing price to income ratio target for a market segment by the government. The policy requires active intervention by the government with regard to the targeted sector. We use a simple model of the housing market with a homeownership affordability target to derive the market implications of such targets. In the presence of uncertainty and resource constraints, the objective of homeownership affordability is achieved for the targeted group at the expense of greater volatility in residential construction activity. When the size of the targeted sector is significant in size, there are spillover price and crowding out effects on the non-targeted housing market segment. This results in political pressure on the government to expand homeownership affordability targets to increasing segments of the population. Housing price to income ratios tend to be fairly constant over time and across targeted groups, the housing supply is relatively price inelastic and the income elasticity of housing demand is less than one. The Singapore government intervenes extensively in the housing sector to ensure homeownership affordability, with a resulting homeownership rate of 91 percent for the resident population. The above hypotheses regarding the implications of setting housing price to income ratio targets are tested using the Singapore housing market. The experience and data for Singapore were found to support the above hypotheses.